2021
DOI: 10.1080/22221751.2021.1917309
|View full text |Cite
|
Sign up to set email alerts
|

Pan-coronavirus fusion inhibitors possess potent inhibitory activity against HIV-1, HIV-2, and simian immunodeficiency virus

Abstract: EK1 peptide is a membrane fusion inhibitor with broad-spectrum activity against human coronaviruses (CoVs). In the outbreak of COVID-19, we generated a lipopeptide EK1V1 by modifying EK1 with cholesterol, which exhibited significantly improved antiviral activity. In this study, we surprisingly found that EK1V1 also displayed potent crossinhibitory activities against divergent HIV-1, HIV-2, and simian immunodeficiency virus (SIV) isolates. Consistently, the recently reported EK1 derivative EK1C4 and SARS-CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…We found that the S protein of SARS-CoV-2 has a much higher fusogenic activity than the S protein of SARS-CoV and its HR2-derived fusion inhibitors exhibits potent and broad-spectrum inhibitory activity against divergent human CoVs [ 31 , 32 ]. Interestingly, several pan-CoV fusion inhibitors, including EK1V1, EK1C4, and IPB02, were serendipitously found to have cross-inhibitory activities against divergent HIV-1, HIV-2, and simian immunodeficiency virus (SIV) isolates [ 51 ]. In this study, we continued our efforts to develop SARS-CoV-2 fusion inhibitors with improved pharmaceutical profiles.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the S protein of SARS-CoV-2 has a much higher fusogenic activity than the S protein of SARS-CoV and its HR2-derived fusion inhibitors exhibits potent and broad-spectrum inhibitory activity against divergent human CoVs [ 31 , 32 ]. Interestingly, several pan-CoV fusion inhibitors, including EK1V1, EK1C4, and IPB02, were serendipitously found to have cross-inhibitory activities against divergent HIV-1, HIV-2, and simian immunodeficiency virus (SIV) isolates [ 51 ]. In this study, we continued our efforts to develop SARS-CoV-2 fusion inhibitors with improved pharmaceutical profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Yuxian He and co-workers have synthesized a lipo-peptide EK1V1 by modifying EK1 with cholesterol, which exhibited significantly improved antiviral activity. EK1V1 displayed potent cross inhibitory activities against divergent HIV-1, HIV-2, and simian immunodeficiency virus (SIV) (Yu et al 2021 ). Another EK1 derivative, the lipo-peptide EK1C4 increases the inhibitory activity against the SARS-CoV-2 and HIV-1 infection (Xia et al 2020 ).…”
Section: Lipid Anchor and Virus Entry Inhibitormentioning
confidence: 99%
“…EK1C4 can effectively protect mice from infection by intranasal administration before or after the HCoV-OC43 attack, which indicates that EK1C4 can be used to prevent and treat infections caused by SARS-CoV-2 and other emerging coronaviruses [ 15 ]. Moreover, another lipopeptide, EK1V1, generated by adding cholesterol to the EK1, exhibits significantly improved antiviral activity against human coronaviruses, HIV-1, HIV-2, and SIV (simian immunodeficiency virus) [ 70 ], which indicated that lipopeptide EK1 and its derivatives are promising virus fusion inhibitors with broad-spectrum antivirals.…”
Section: Targets For Pan-coronavirus Inhibitorsmentioning
confidence: 99%